200k views
5 votes
2x + 3y ≥ 6
3x + 2y ≤ 6
(1.5, 1)
(0.5.2)
(-1.2.5)
(-2.4)​

User Votive
by
4.6k points

1 Answer

1 vote

Answer:

Explanation:

x - 3y )(9x - 2y ) 17. (3x - 4 ) 2. 19. (x + 12). (x - 12) 21. (4y + 1)(4y - 1) 23. 4(3y + 2)(3y ... -4 -3 -2 -1 0. 7. s ≥. 3_. 2. 5. -5. 4321. -4 -3 -2 -1 0. 9. 40 bags. 11. n ≤ -3. 5. -5. 4321 ... 31. (-3, -4) 33. infinite solutions 35. (-1.5, -2). 37. y x. О y = 2x + 6 y = 2x - 1 ... at (1, 8). 79b. h (d ) = -2(d - 1.2 5) 2 + 12.5; It shifted the graph up 4.5 ft.

User Ferdinand Beyer
by
4.7k points